Translation Shifts in The Indonesian Subtitle of The Revenant Film: A Systemic Functional Linguistics Approach - Kania Widianti Suherman (Universitas Pendidikan Indonesia (UPI), 2018)
This research aims to analyse translation shifts of nominal and verbal groups found in the Indonesian subtitle of The Revenant film, and observe how translation shifts affect the meanings. This study employs a descriptive qualitative method. The data are taken from the transcription and subtitle of The Revenant film. This study follows Halliday and Matthiessen’s (2004) concept of nominal group and verbal group (transitivity) and Catford’s (1965) theory of translation shifts which includes level shift, structure shift, unit shift, class shift, and intra-system shift. The analysis shows that the process of translating involves single and double translation shifts. In nominal groups, the shifts were dominated by unit + intra-system shifts (40.87%). While in verbal groups, the shifts were dominated by intra-system shift (71.70%). Both shifts slightly affect the meanings of the translated text. This study suggests that linguistic analysis could provide research-based samples of how the experts conducted translation. Keywords: translation shift, nominal group, verbal group, the revenant, film subtitle